Clinical impacts of the concomitant use of L-asparaginase and total parenteral nutrition containing L-aspartic acid in patients with acute lymphoblastic leukemia - Ko, Minoh; Kim, Myeong Gyu; Yoon, Sung-Soo; Kim, In-Wha; Suh, Sung Yun; Cho, Yoon-Sook; Oh, Jung Mi (Frontiers in Nutrition, 2023)
Introduction L-asparaginase (ASNase) depletes L-asparagine and causes the death of leukemic cells, making it a mainstay for the treatment of acute lymphoblastic leukemia (ALL). However, ASNase's activity can be inhibited by L-aspartic acid (Asp), which competes for the same substrate and reduces the drug's efficacy. While many commercially used total parenteral nutrition (TPN) products contain Asp, it is unclear how the concomitant use of TPNs containing Asp (Asp-TPN) affects ALL patients treated with ASNase. This propensity-matched retrospective cohort study evaluated the clinical effects of the interaction between ASNase and Asp-TPN. Methods The study population included newly diagnosed adult Korean ALL patients who received VPDL induction therapy consisting of vincristine, prednisolone, daunorubicin, and Escherichia coli L-asparaginase between 2004 and 2021. Patients were divided into two groups based on their exposure to Asp-TPN: (1) Asp-TPN group and (2) control group. Data, including baseline characteristics, disease information, medication information, and laboratory data, were collected retrospectively. The primary outcomes for the effectiveness were overall and complete response rates. Relapse-free survival at six months and one year of treatment were also evaluated. The safety of both TPN and ASNase was evaluated by comparing liver function test levels between groups. A 1:1 propensity score matching analysis was conducted to minimize potential selection bias. Results The analysis included a total of 112 ALL patients, and 34 of whom received Asp-TPN and ASNase concomitantly. After propensity score matching, 30 patients remained in each group. The concomitant use of Asp-TPN and ASNase did not affect the overall response rate (odds ratio [OR] 0.53; 95% confidence interval [CI] = 0.17–1.62) or the complete response rate (OR 0.86; 95% CI = 0.29–2.59) of the ASNase-including induction therapy. The concomitant use of Asp-TPN and ASNase also did not impact relapse-free survival (RFS) at six months and one year of treatment (OR 1.00; 95% CI = 0.36–2.78 and OR 1.24; 95% CI, 0.50–3.12, respectively). The peak levels of each liver function test (LFT) and the frequency of LFT elevations were evaluated during induction therapy and showed no difference between the two groups. Conclusion There is no clear rationale for avoiding Asp-TPN in ASNase-treated patients.